Cover Image, Volume 137, Issue 45. Issue 45 (28th August 2020) - Harito, Christian; Lledo, Rosa C.; Bavykin, Dmitry V.; Moshrefi‐Torbati, Mohamed; Islam, Aminul; Yuliarto, Brian; Walsh, Frank C.
Abstract : The cover image created by Christian Harito and colleagues shows an array of TiO2 nanotubes with characteristic diameter ≈140 nm and the length of ≈1.5 microns. The image was created by anodic oxidation of a titanium substrate and used as a template for soft polydimethylsiloxane (PDMS) moulding. And the optimal moulding process was developed by a combination of silanization, use of solvent, the application of vacuum, and hydraulic‐pressing. The hydraulic‐pressing significantly improved the infiltration of PDMS into the pores of nanotubular array resulting in formation of PDMS nano‐bumps and worm‐like structures after separation of the polymer from the template. DOI: 10.1002/app.49795